To determine the relation of mean platelet volume with diabetes mellitus - Milind Jivanlal Manvar,; Rajesh Sukumar Roy,; Viralkumar Mohanbhai Jadav,; Amalkumar Bankimchandra Bhattacharya, (Asian Journal of Medical Sciences, 2022)
Background: Diabetes mellitus (DM) is a complex metabolic disorder portrayed by chronic hyperglycemia bringing about intricacies influencing the peripheral nerves, kidneys, eyes, and macrovascular structures. Mean platelet volume (MPV) is also considered to impact the advancement of microvascular complications of diabetes mellitus which has been looked for in this study. Aims and Objectives: The aims of this study were as follows: (1) To study association of MPV with Nephropathy and Retinopathy in Diabetes. (2) To Study correlation of MPV with hemoglobin A1c (HbA1C), fasting blood sugar, post-prandial blood sugar, and body mass index (BMI). Materials and Methods: This was an observational study conducted over 18 months period on patients (both males and females) seeking medical attention for newly diagnosed or previously diagnosed DM. Selective sampling technique was used and 200 diabetic patients were enrolled in the study during the study period. Results: (1) The incidence of retinopathy and increased Hba1c was significantly higher in poorly controlled diabetics as compared to controlled diabetics. (2) In good glycemic control group, mean MPV was 8.58 fL and, in poor glycemic control group, mean MPV was 10.21 fL. Conclusion: There was a positive correlation between MPV and HbA1C, microalbuminuria, BMI, fasting, and post-prandial blood sugar levels. There was no significant association between MPV and retinopathy.